Chapter "The Root of All Evil is Inactivity" The Response of French Psychiatrists to New Approaches to Patient Work and Occupation, 1918-1939 - Freebody, Jane (Springer Nature, 2021)
This chapter focuses on the varied responses of French psychiatrists to new theories of patient occupation emerging after World War I (1914-18).